The SAGE Handbook of social media research methods - Quan-Haase, Anabel; Sloan, Luke (London : SAGE Publications Ltd, 2022)
The SAGE Handbook of Social Media Research Methods spans the entire research process, from data collection to analysis and interpretation. This second edition has been comprehensively updated and expanded, from 39 to 49 chapters. In addition to a new section of chapters focussing on ethics, privacy and the politics of social media data, the new edition provides broader coverage of topics such as: (1) Data sources; (2) Scraping and spidering data; (3) Locative data, video data and linked data; (4) Platform-specific analysis; (5) Analytical tools; and (6) Critical social media analysis. Written by leading scholars from across the globe, the chapters provide a mix of theoretical and applied assessments of topics, and include a range of new case studies and data sets that exemplify the methodological approaches. This Handbook is an essential resource for any researcher or postgraduate student embarking on a social media research project. PART 1: Conceptualising and Designing Social Media Research; PART 2: Collecting Data; PART 3: Qualitative Approaches to Social Media Data; PART 4: Quantitative Approaches to Social Media Data; PART 5: Diverse Approaches to Social Media Data; PART 6: Research and Analytical Tools; PART 7: Social Media Platforms; and PART 8: Privacy, Ethics and Inequalities.
Description based on XML content.
Includes index.
Keywords: Social media -- Research -- Handbooks, manuals, etc; Social media -- Research -- Methodology